1990
DOI: 10.1073/pnas.87.20.7907
|View full text |Cite
|
Sign up to set email alerts
|

Possible deletion of a developmentally regulated heavy-chain variable region gene in autoimmune diseases.

Abstract: Several autoantibody-associated variable region (V) genes are preferentially expressed during early ontogenic development, suggesting strongly that they are of developmental and physiological importance. As such, it is possible that polymorphisms in one or more of these genes may alter susceptibility to autoimmune disease. We have searched extensively for a probe related to a developmentally regulated V gene that has the power to differentiate among highly homologous V genes in human populations. Using such a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…12,25 A duplication polymorphism of two genes, IGHV3-30 and IGHV4-28, was also described. [29][30][31] The duplicates in the latter case were shown to be in a tandem configuration. 31 The pseudogene IGHV3-29 was shown to be in a present/absent manner in this duplicated region.…”
Section: Discussionmentioning
confidence: 99%
“…12,25 A duplication polymorphism of two genes, IGHV3-30 and IGHV4-28, was also described. [29][30][31] The duplicates in the latter case were shown to be in a tandem configuration. 31 The pseudogene IGHV3-29 was shown to be in a present/absent manner in this duplicated region.…”
Section: Discussionmentioning
confidence: 99%
“…Results from similar analysis indicated that V3-30b (hv3005) was absent in the other three patients but that one or more V3-30 elements were present in each of the controls. High frequency of deletion of V3-30b in RA patients has been shown by others [39].…”
Section: Representation Of Individual V H Genes In Peripheral Blood Bmentioning
confidence: 92%
“…It has been reported that certain polymorphisms within the human Ig Vk locus are associated with rheumatoid arthritis (11,12). In addition, it has been shown that polymorphisms in the two human VH genes, both of which can encode anti-DNA Abs are related with the development of autoimmune diseases (13)(14)(15). Other study has also suggested that VH haplotypes may have linkage with autoAb production (16).…”
Section: Introductionmentioning
confidence: 99%